Molecular basis of Tousled-Like Kinase 2 activation - Mortuza, Gulnahar B. (2018)
Tousled-like kinases (TLKs) are required for genome stability and normal development in numerous organisms and have been implicated in breast cancer and intellectual disability. In humans, the similar TLK1 and TLK2 interact with each other and TLK activity enhances ASF1 histone binding and is inhibited by the DNA damage response, although the molecular mechanisms of TLK regulation remain unclear. Here we describe the crystal structure of the TLK2 kinase domain. We show that the coiled-coil domains mediate dimerization and are essential for activation through ordered autophosphorylation that promotes higher order oligomers that locally increase TLK2 activity. We show that TLK2 mutations involved in intellectual disability impair kinase activity, and the docking of several small-molecule inhibitors of TLK activity suggest that the crystal structure will be useful for guiding the rationale design of new inhibition strategies. Together our results provide insights into the structure and molecular regulation of the TLKs.